Theres a saying: Dividing fractions dont ask why, just flip the second and multiply.
so a/b / c/d = a/b * d/c
-8/2 * -3/6
1. cross - cancel common factor 2
4/2 * -3/3
2. Multiply
-4(-3)/ 2*3
3. multiply numbers
--12/2*3
- -12/6
4. Apply fraction rule -a/b=- a/b
=-(-12/6)
5. divide
= -(-2)
6. Apply rule -(-a)=a
=2
Your answer would be 2
Answer:
The volume of the composite figure is:
Step-by-step explanation:
To identify the volume of the composite figure, you can divide it in the known figures there, in this case, you can divide the figure in a cube and a pyramid with a square base. Now, we find the volume of each figure and finally add the two volumes.
<em>VOLUME OF THE CUBE.
</em>
Finding the volume of a cube is actually simple, you only must follow the next formula:
- Volume of a cube = base * height * width
So:
- Volume of a cube = 6 ft * 6 ft * 6 ft
- <u>Volume of a cube = 216 ft^3
</u>
<em>VOLUME OF THE PYRAMID.
</em>
The volume of a pyramid with a square base is:
- Volume of a pyramid = 1/3 B * h
Where:
<em>B = area of the base.
</em>
<em>h = height.
</em>
How you can remember, the area of a square is base * height, so B = 6 ft * 6 ft = 36 ft^2, now we can replace in the formula:
- Volume of a pyramid = 1/3 36 ft^2 * 8 ft
- <u>Volume of a pyramid = 96 ft^3
</u>
Finally, we add the volumes found:
- Volume of the composite figure = 216 ft^3 + 96 ft^3
- <u>Volume of the composite figure = 312 ft^3</u>
Yes, all of the rhombuses have 2 pairs of parallel side.
Easy, its b because that is the average deviation
Answer:
b) 2x + y = -4
Step-by-step explanation:
To go from the Point-Slope Formula [y - y₁ = m(x - x)₁] to the Slope-Intercept Formula [y = mx + b], move -1 to the RIGHT side of the equivalence symbol to get this: y = -2x - 4. Although this is a correct answer choice, this is NOT what the question is looking for because you have to go an extra step further, Standard Formula. To go from the Slope-Intercept Formula to the Standard Formula [Ax + By = C], move 2x to the LEFT side of the equivalence symbol, and you will end up with this: 2x + y = -4. So, your answer is b).